Upaya Merekonstruksi Posisi Bahasa Agama dalam Memahami Yang Sakral dan Profan - Mahfud Mahfud (Proceedings of Annual Conference for Muslim Scholars, 2017)
This article attempts to explain in the light of the position of "religious language". The language of religion which is considered the most sacred thing as it pertains to the faith of Islam. In the extra courage to break the required purity. In that regard then this article tries to give a more comprehensive explanation of the prestige or position in the sacred and the profane "religious language". Qur'an as a revelation of the Supreme Court at the level of an object is now an in-depth study in finding the answer to the question whether the language of the Quran in Arabic it is the "language" of God? In answering that question of course there is a profound difference in providing answers to the question. The first answer is believed with certainty that religious language is a language that certainly from God and ultimately language or the language of religion is considered sacred writings. At this stage, all the languages that use religious language are considered "sacred". While second the considers the existing religious language is the language. This means that religious language to use human language and the results of the human culture. This second opinion is based on the argument that God does not have a language and writing. Language and writing are the human territories. Therefore this paper tries to give the discussion to distinguish the sacred and the profane in the religious language.